DEVELOPING A OF PROBLEM-BASED LEARNING MODEL OF COOPERATIVE SETTING TO ENHANCE MATHEMATICAL POWER AND SOCIAL SKILLS - ., Japar (Journal of Educational Science and Technology, 2015)
The research aimed at discovering the description of mathematics learning in MTs and obtaining PBMSK (Problem-based learning of Cooperative Setting) model which was valid, practical, and effective to improve mathematical power and social skills of class VIII students at MTs. Negeri (Public MTs) Model Makassar. The study was a research and development which referred to Plompâs (1997) model development. The data analysis was conducted quantitatively to answer whether the model developed had already met valid, practical and effective criteria. The products of the study consisted of: model book, teacherâs book, studentâs book, lesson plan, studentâs worksheet, and learning result test with the validity level 3.66 (extremely valid) which had met valid criteria. The implementation of model 1.88 (implemented entirely) had met practicality criteria. The effectiveness of model consisted of: learning completeness 92.15%, learning management 3.84 (excellent), studentâs responses on PBMSK model: (1) expressed delight 96.25%, expressed interested 95.0%, and (3) studentâs worksheet and text book easy to read 92.5%, interesting 95%, simple language 92.5%, and the studentsâ activities were fairly high and still at the ideal time interval tolerance which had been determined. The results indicated that it had met effective criteria. Therefore, the objective to obtain qualified PBMSK model which fulfilled valid, practical, and effective criteria had been achieved.Keywords:Â  Model development, PBMSK model, valid, practical, and effectiveÂ